BIOMARKER GEOCHEMISTRY OF PALEOGENE CRUDE OILS AND SOURCE ROCKS FROM THE RAOYANG SAG, BOHAI BAY BASIN, NE CHINA: AN OIL – SOURCE ROCK CORRELATION STUDY. (21st December 2021) - Su, Shengmin; Jiang, Youlu
Abstract : This study presents a systematic geochemical analysis of Paleogene crude oils and source rocks from the Raoyang Sag in the Jizhong sub‐basin of the Bohai Bay Basin (NE China). The geochemical characteristics of fifty‐three oil samples from wells in four sub‐sags were analysed using gas chromatography (GC) and gas chromatography – mass spectrometry (GC‐MS). Twenty core samples of mudstones from Members 1 and 3 of the Eocene‐Oligocene Shahejie Formation were investigated for total organic carbon (TOC) content and by Rock‐Eval pyrolysis and GC‐MS to study their geochemistry and hydrocarbon generation potential. The oils were tentatively correlated to the source rocks. The results show that three groups of crude oils can be identified. Group I oils are characterized by high values of the gammacerane index and low values of the ratios of Pr/Ph, Ts/Tm, 20S/(20S+20R) C29 steranes, ββ/(ββ+αα) C29 steranes, C27 diasteranes/ C27 regular steranes and C27 /C29 steranes. These oils have the lowest maturity and are interpreted to have originated from a source rock containing mixed organic matter deposited in an anoxic saline lacustrine environment. The biomarker parameter values of Group III oils are the opposite to those in Group I, and are interpreted to indicate a highly mature, terrigenous organic matter input into source rocks which were deposited in suboxic to anoxic freshwater lacustrine conditions. The parameter values of Group II oils are between those of the oils in Groups I and III, and are interpreted to indicate that the oils were generated from mixed organic matter in source rocks deposited in an anoxic brackish–saline or saline lacustrine environment. The results of the source rock analyses show that samples from Member 1 of the Shahejie Formation were deposited in an anoxic, brackish – saline or saline lacustrine environment with mixed organic matter input and are of low maturity. Source rocks in Member 3 of the Shahejie Formation were deposited in a suboxic to anoxic, brackish – saline or freshwater lacustrine environment with a terrigenous organic matter input and are of higher maturity. Correlation between rock samples and crude oils indicates that Group I oils were probably derived from Member 1 source rocks, while Group III oils were more likely generated by Member 3 source rocks. The Group II oils with transitional characteristics are likely to have a mixed source from both sets of source rocks.